Using the iPlant Collaborative Discovery Environment. Issue 1 (1st June 2013) - Oliver, Shannon L.; Lenards, Andrew J.; Barthelson, Roger A.; Merchant, Nirav; McKay, Sheldon J.
Abstract: The iPlant Collaborative is an academic consortium whose mission is to develop an informatics and social infrastructure to address the "grand challenges" in plant biology. Its cyberinfrastructure supports the computational needs of the research community and facilitates solving major challenges in plant science. The Discovery Environment provides a powerful and rich graphical interface to the iPlant Collaborative cyberinfrastructure by creating an accessible virtual workbench that enables all levels of expertise, ranging from students to traditional biology researchers and computational experts, to explore, analyze, and share their data. By providing access to iPlant's robust data‐management system and high‐performance computing resources, the Discovery Environment also creates a unified space in which researchers can access scalable tools. Researchers can use available Applications (Apps) to execute analyses on their data, as well as customize or integrate their own tools to better meet the specific needs of their research. These Apps can also be used in workflows that automate more complicated analyses. This module describes how to use the main features of the Discovery Environment, using bioinformatics workflows for high‐throughput sequence data as examples. Curr. Protoc. Bioinform . 42:1.22.1‐1.22.26. © 2013 by John Wiley & Sons, Inc.